Testing sample stability using four storage methods and the macroalgae Ulva and Gracilaria. (28th January 2015) - Oczkowski, Autumn; Thornber, Carol S.; Markham, Erin E.; Rossi, Ryann; Ziegler, Amanda; Rinehart, Shelby
Abstract: Concern over the relative importance of different sample preparation and storage techniques frequently used in stable isotope analysis of particulate nitrogen (δ 15 N) and carbon (δ 13 C) prompted an experiment to determine how important such factors were to measured values in marine organisms. We stored the marine macroalgae Ulva and Gracilaria in four different ways and analyzed replicates every three months over the course of a year to assess treatment effects on stability. Treatments consisted of algae dried at 65°C, ground to a powder, and stored in a desiccator until analysis; algae left in a drying oven or in a freezer and processed (dried and ground) just prior to analysis, as well as some dried, ground samples kept out in the lab and reanalyzed quarterly for 12 months. Concurrently, to assess the ecological range in isotope values over the course of a year, samples were freshly collected from the same location and analyzed along with the other treatments at each time step. Neither storage technique nor time had an impact on either δ 15 N or δ 13 C values or the %N and %C of the algae tissues. There were clear and consistent differences between species and some large seasonal differences in the freshly collected samples. The interspecies differences and seasonal ranges of values underscore the stability associated with method and duration of sample storage.